Volatile Sedation for Acute Respiratory Distress Syndrome Patients on Venovenous Extracorporeal Membrane Oxygenation and Ultraprotective Ventilation. (8th January 2021) - Grasselli, Giacomo; Giani, Marco; Scaravilli, Vittorio; Fumagalli, Benedetta; Mariani, Carminia; Redaelli, Sara; Lucchini, Alberto; Zanella, Alberto; Patroniti, Nicolò; Pesenti, Antonio; Foti, Giuseppe
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Patients on extracorporeal support for severe acute respiratory distress syndrome may require a prolonged period of deep sedation. In these patients, volatile sedation may represent a valid alternative to IV drugs. The aim of our study was to describe the feasibility of volatile sedation in a large cohort of acute respiratory distress syndrome patients undergoing venovenous extracorporeal membrane oxygenation and ultraprotective ventilation. Design: Retrospective monocentric study. Setting: Adult ICU, ASST Monza, Italy. Patients: Adult patients who underwent volatile sedation with isoflurane during venovenous extracorporeal membrane oxygenation between 2009 and 2019. Interventions: Isoflurane was delivered via the AnaConDa system. The sedation level, hemodynamics, and laboratory tests were compared between the volatile sedation phase and the IV sedation phases before and after the isoflurane sedation period. Measurements and Main Results: About 74 patients (50 yr [43–56 yr]) were included. Median duration of venovenous extracorporeal membrane oxygenation support was 22 days (14–51 d). Volatile sedation started on day 3 (2–6) of extracorporeal membrane oxygenation support, and its median duration was 7 days (4–13 d), ranging from 1 to 38 days. A total of 970 venovenous extracorporeal membrane oxygenation days were analyzed. During the volatile phase, the sedation level was slightly deeper (bispectral index 39 ± 6) compared with the IV phase before and after isoflurane (42 ± 8 and 43 ± 9, respectively, p < 0.001). Requirements of fentanyl and remifentanyl were reduced during the volatile phase. Minor differences in hemodynamics were observed during volatile sedation: mean arterial pressure was lower (75 ± 13 vs 79 ± 14 and 80 ± 15; p < 0.001), whereas cardiac output was higher (8.5 ± 1.9 vs 7.9 ± 1.8 and 8.0 ± 1.8; p = 0.003). Aspartate aminotransferase levels were lower during the volatile sedation phases ( p < 0.001), whereas alanine aminotransferase, triglycerides, and creatine phosphokinase were more altered during the IV sedation phase before isoflurane ( p < 0.001). Conclusions: Volatile sedation represents an alternative to IV agents to achieve long-term deep sedation in critically ill patients on extracorporeal membrane oxygenation undergoing ultraprotective ventilation.